2005
DOI: 10.1063/1.1885183
|View full text |Cite
|
Sign up to set email alerts
|

Nanomechanical characterization of cavity growth and rupture in hydrogen-implanted single-crystal BaTiO3

Abstract: A thermodynamic model of cavity nucleation and growth in ion-implanted single-crystal BaTiO 3 layer is proposed, and cavity formation is related to the measured mechanical properties to better understand hydrogen implantation-induced layer transfer processes for ferroelectric thin films. The critical radius for cavity nucleation was determined experimentally from blistering experiments performed under isochronal anneal conditions and was calculated using continuum mechanical models for deformation and fracture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…2 and from AFM/nanoindentation characterization, the thickness ͑h͒ of the delaminating layer is 0.50 m, and the interdistance ͑D͒ of bubbles is found to be 16 m. The initial diameter ͑b͒ of blisters is 4.0 m. The material properties are assumed to be linear elastic, with Young's modulus for the layers taken to be 120.0 GPa, and Poisson's ratio ͑͒ is assumed to be 0.3. 17 Three-dimensional 8-node brick elements are adopted for the both top and bottom layers for FEM simulation. All the nodes at the bottom layer representing the donor wafer are held at fixed positions.…”
Section: ͑6͒mentioning
confidence: 99%
See 3 more Smart Citations
“…2 and from AFM/nanoindentation characterization, the thickness ͑h͒ of the delaminating layer is 0.50 m, and the interdistance ͑D͒ of bubbles is found to be 16 m. The initial diameter ͑b͒ of blisters is 4.0 m. The material properties are assumed to be linear elastic, with Young's modulus for the layers taken to be 120.0 GPa, and Poisson's ratio ͑͒ is assumed to be 0.3. 17 Three-dimensional 8-node brick elements are adopted for the both top and bottom layers for FEM simulation. All the nodes at the bottom layer representing the donor wafer are held at fixed positions.…”
Section: ͑6͒mentioning
confidence: 99%
“…At the bottom of the BaTiO 3 donor substrate layer, pressure increasing linearly in time is imposed up to a maximum of 200 MPa, as calculated using bubble geometry. 17 As the internal pressure of a cavity increases, both cavity growth and debonding at the interface occur. As shown in Fig.…”
Section: ͑6͒mentioning
confidence: 99%
See 2 more Smart Citations
“…In previous work, the authors showed that the layer splitting mechanism induced a change in the hardness and Young's modulus of the implanted BaTiO 3 donor wafer. 28 This can be explained by an increase in strain near the bubble region during the layer exfoliation process. After postbond annealing, the micro-Raman curve is almost identical to the unprocessed, single crystal BaTiO 3 .…”
Section: Microstructure Of Ion Damaged Batiomentioning
confidence: 99%